Scalable Software Testing and Verification for Industrial-Scale Systems: The Challenges - Mjeda, Anila; Botterweck, Goetz (Electronic Communications of the EASST, 2019)
In this position paper, we argue that more collaborative research is needed to increase the use of research-led verification and testing techniques in industrial-scale projects. We focus on the a) practical applicability and scalability of verification and testing techniques in industrial projects, and b) to autonomous systems. We identify the challenges involved and bring forward some initial suggestions.